Hubungan Persepsi Dukungan Sosial dengan Resiliensi Anak & Remaja Indonesia Selama Pandemi COVID-19 - Anandita Ramadhyani; Hedi Wahyudi (Bandung Conference Series: Psychology Science, 2022)
Abstract. The COVID-19 pandemic is a collective event that affecting psychological conditions and brings adversities, including for Indonesian children and adolescents. Help and support perceived by children and adolescents helps them to get out of the difficult situations during the pandemic. This study aims to find out the correlation between perceived social support and resilience in Indonesia children and adolescents during the COVID-19 pandemic. This study was conducted using a quantitative approach and correlational methods through an online survey with a sample of 3,115 children and adolescents aged 10-18 years living in Indonesia. Measuremets were done using the Multidimensional Scale of Perceived Social Support (MSPSS) to measure perceived social support and Children and Youth Resilience Measure Revision (CYRM-R) to measure resilience. The analysis technique was carried out using Spearman Rank correlation wih the results of 0.577 and p-value (Sig.) = 0.000 < α = 0.01 which showed a positive and moderate correlation between perceived social support and resilience. Abstrak. Pandemi COVID-19 merupakan kejadian kolektif yang mempengaruhi kondisi psikologis dan membawa kesulitan, termasuk bagi anak dan remaja Indonesia. Bantuan dan dukungan yang diperspsi oleh anak dan remaja membantu mereka untuk keluar dari keadaan sulit di masa pandemi. Penelitian ini ditujukan unuk mencari tahu keterkaitan antara persepsi dukungan sosial dengan resilensi pada anak dan remaja Indonesia selama pandemi COVID-19. Penelitian dilakukan menggunakan pendekatan kuantitatif dan metode korelasional melalui online survey dengan sampel sebanyak 3,115 anak dan remaja berusia 10-18 tahun di wilayah Indonesia. Pengukuran dilakukan menggunakan Multidimensional Scale of Perceived Social Support (MSPSS) untuk mengukur persepsi dukungan sosial dan Child and Youth Resilience Measure Revision (CYRM-R) untuk mengukur resiliensi. Teknik analisis dilakukan menggunakan korelasi Rank Spearman engan hasil 0.577 dan p-value (Sig.) = 0.000 < α = 0.01 yang menunjukkan koreasi sedang (moderate) yang positif antara persepsi dukungan sosial dengan resiliensi.